2019
DOI: 10.1016/j.chom.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A Surface-Induced Asymmetric Program Promotes Tissue Colonization by Pseudomonas aeruginosa

Abstract: The opportunistic human pathogen Pseudomonas aeruginosa effectively colonizes host epithelia using pili as primary adhesins. Here we uncover a surfacespecific asymmetric virulence program that enhances P. aeruginosa host colonization. We show that when P. aeruginosa encounters surfaces, the concentration of the second messenger c-di-GMP increases within a few seconds. This leads to surface adherence and virulence induction by stimulating pili assembly through activation of the c-di-GMP receptor FimW. Surface-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
159
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(195 citation statements)
references
References 65 publications
21
159
2
2
Order By: Relevance
“…Our findings, of surface‐driven growth of filaments, suggest that the fimbriae/pili‐initiated attachment is required for lag‐phase bacteria to divide continuously without separation—a correlation yet to be elucidated. A particularly interesting finding is that surface attachment can cause “asymmetric cell divisions”, through which a bacterium adhering to a surface to can generate two different daughter phenotypes . Thus, the progeny within each filament grown on a surface is an interesting topic for exploration.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings, of surface‐driven growth of filaments, suggest that the fimbriae/pili‐initiated attachment is required for lag‐phase bacteria to divide continuously without separation—a correlation yet to be elucidated. A particularly interesting finding is that surface attachment can cause “asymmetric cell divisions”, through which a bacterium adhering to a surface to can generate two different daughter phenotypes . Thus, the progeny within each filament grown on a surface is an interesting topic for exploration.…”
Section: Resultsmentioning
confidence: 99%
“…citri, it has been indicated that the PilZ-FimX EAL -c-di-GMP complex is responsible for regulation of T4P biogenesis (Guzzo et al, 2013). Recent findings showed that the P. aeruginosa fimW encoding a PilZ protein, adjacent to fimX in the chromosome, is a c-di-GMP high-affinity binding protein and regulates T4P dynamics, as well as being necessary for T4P-based attachment (Laventie et al, 2019). Cryoelectron tomography combined with protein-protein interaction assays revealed that the N terminus of PilN binds to PilM in the cytoplasm, then PilM binds to PilT and PilB, two ATPases that power assembly and disassembly of T4P, respectively (Kolappan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that some pathogens are able to induce virulence genes expression on surface contact, and that T4P play an important role in this process (Laventie et al, 2019). One of the major virulence factors of Xoo is the T3SS (Buttner and Bonas, 2010).…”
Section: Positive Regulation Of T3ss Genes Expression By Pilnmentioning
confidence: 99%
See 2 more Smart Citations